Exercise training-induced changes in respiratory muscles - Powers, S. K.; Coombes, J.; Demirel, H. (Sports Medicine, 1997)
Interest in the adaptive strategies of respiratory muscles in response to exercise training has grown in recent years. Animal studies have clearly demonstrated that regular endurance exercise training results in small but significant increases in oxidative and antioxidant enzyme activities in both inspiratory and expiratory muscles. Further, exercise training has been shown to promote a shift in the fast myosin heavy chain isoforms (e.g. from type IIb to IId) within the costal diaphragm of endurance-trained rodents. Human studies using numerous respiratory muscle training programmes have shown that respiratory muscle training results in an increased work capacity of the ventilatory musculature. However, the issue of whatever respiratory muscle training improves whole body endurance capacity remains controversial. Although some authors have reported that ventilatory muscle training results in improved whole body exercise, many investigators argue that respiratory muscle performance does not limit high intensity exercise tolerance or influence maximum oxygen table uptake (VO2max). The explanation for the divergent findings is unclear but may be due to variance in the exercise tasks used to evaluate exercise endurance. This is an interesting area for future research.